The Dialogue of the Constitutional Court with the Ordinary Courts: The Developments in Thirty Years - Keturakienė, Airė; Murauskas, Donatas (Vilnius University Open Series, 2024)
We discuss the interaction between the Constitutional Court of the Republic of Lithuania and the ordinary courts over three decades. First, we analyse the implementation of the right and obligation of ordinary courts to apply to the Constitutional Court. Also, we consider the possibility for the Constitutional Court to suspend the execution of the ordinary court decision which is associated with the emergence of an individual constitutional complaint. Finally, we overview the reopening of the ordinary court proceedings after the ruling of the Constitutional Court. We discuss in which cases the interaction of the courts can be identified as the judicial dialogue.
Keywords: Constitutional Court; judicial dialogue; courts; individual constitutional complaint